Implementation of Government Accounting Standards in the Financial Statements of BLUD RSUD dr. RM. Djoelham Binjai - Putri Kesha Abelia; Datin Qintara; Iskandar Muda (CV. Kalimasada Group, 2025)
This study analyzes the application of Government Accounting Standards (SAP) in the financial management of the Regional Public Service Agency (BLUD) at RSUD dr. Djoelham Binjai. The scope of the study includes the application of accrual-based accounting principles to financial statements, including the Budget Realization Report, Balance Sheet, Operational Report, Cash Flow Statement, and Statement of Changes in Equity. The research method used is descriptive qualitative with a deductive approach. Data were collected from secondary sources, including hospital financial reports for 2022-2023, policy documents, and relevant literature. The research findings show that the implementation of SAP in BLUD financial reporting has generally been effective in improving transparency, efficiency, and accountability. However, the study also found some obstacles such as limited human resources in accounting as well as delays in cash flow management. The BLUD system has increased financial flexibility and service productivity in accordance with Permendagri No. 79/2018. The findings indicate the need for improved financial management capacity and stronger coordination between BLUD and local government to optimize public service outcomes.